Body mass index and all‐cause mortality in patients with percutaneous coronary intervention: A dose–response meta‐analysis of obesity paradox. (20th July 2020) - Mei, Xiaofei; Hu, Shengda; Mi, Lijie; Zhou, Yafeng; Chen, Tan
Summary: The association between body mass index (BMI) and mortality of patients with percutaneous coronary intervention (PCI) is still controversial. We hope to explore whether the 'obesity paradox' really exists through this dose–response meta‐analysis. PubMed, Embase and Cochrane databases were systematically searched for eligible studies up to April 2020. The random‐effects restricted cubic spline models were used to evaluate the potential non‐linear relationship between BMI and all‐cause mortality of patients undergoing PCI. Fifteen studies were identified and included total 138 592 participants. The pooled hazard ratio of all‐cause mortality was 0.60 (95% confidence interval: 0.45–0.82) when compared the highest category (mean = 33.32 kg m −2 ) of BMI with the lowest category (mean = 18.89 kg m −2 ). A non‐linear U‐shaped dose–response curve between BMI and the risk of all‐cause mortality was found, with higher mortality rate at BMI lower than 27 kg m −2 and higher than 32 kg m −2 . The 'obesity paradox' does exist after PCI. The association between BMI and the risk of all‐cause mortality for patients undergoing PCI is U shaped, with a nadir of risk at a BMI of 27 to 32 kg m −2 and the highest risk at patients with underweight. The relationship between other prognostic indicators and BMI is worthy of further research.